Evaluation of adenosine deaminase activity for diagnosis of tuberculous pleural effusion - Bhoumik, SK; Rahman, MM; Ibrahim, M; Hiron, MM; Ahamad, M (Journal of Pathology of Nepal, 2013)
Background: Tuberculosis is a leading cause of worldwide preventable morbidity and mortality from an infectious agent. A defi nite diagnosis of tubercular pleural effusion can be diffi cult to make because of low sensitivity and/or specifi city of noninvasive traditional diagnostic tools. This study is done to fi nd out a sensitive and specifi c marker for early diagnosis of tuberculous pleural effusion. Materials and Methods: One hundred and three pleural effusion cases were enrolled in the study, out of which 62 were tuberculous pleural effusion cases and 49 were non-tuberculous cases. Results: Considering 40 U/L as a cut off value for Adenosine deaminase assay level, the test result was positive in 58 out of 62 patients of tuberculosis indicating sensitivity of the test as 94%; however, among 41 non-tuberculous patients, 5 presented ADA activity level more than 40U/L, which lowers the specifi city of the test to 88%. ADA levels were signifi cantly higher in tuberculous than in non tuberculous cases (P value